Kesadaran Religiusitas Orang Dewasa sebagai Solusi bagi Sindrom Perimenopause Menurut Zakiyah Darajat - Nuraeni Nuraeni; Imas Kania Rahman; Budi Handrianto (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This research discusses perimenopause, which is the period leading up to menopause. This period is the final stage of the biological process experienced by women, where at this time there are various changes both in terms of physical, and psychological. This research aims to provide a solution to the discomfort felt by perimenopause women who actually need help, both by themselves and their environment, with their religious knowledge. This paper uses qualitative methods with this type of literature and field research. The results showed that the situation in the tumultuous perimenopause period, can only be faced by getting close to Allah ﷻ, therefore a perimenopausal woman must further deepen her religious knowledge. The religious knowledge possessed by a perimenopause woman will automatically help fortify her to deal with the turmoil of perimenopause accompanied by the full support of family and the environment. The authors hope that this study can give color to the study of Islamic counseling guidance for adults with cases of perimenopause, and contribute information about all matters related to the perimenopause period to government and private institutions and the wider community so that the resilience of Muslim households can be maintained in the context of feel Calm, love and affection.